Premature Newborns with the Potential to Develop Special Health Needs: An Approach by Triangulation of Methods - Rosane Meire Munhak da Silva; Gabriela Dominicci de Melo Casacio; Adriana Zilly; Claudia Silveira Viera; Eliane Tatsch Neves; Elsa Maria de Oliveira Pinheiro Melo; Débora Falleiros de Mello (Universidad de La Sabana, 2024)
Introduction: Maternal recognition of special health needs of premature babies is essential, given the importance of early stimuli after discharge to strengthen child development. Objective: To identify premature newborns with potential factors for the development of special health needs and describe maternal recognition of these factors. Materials and methods: Qualitative and quantitative study, performed using a triangulation method, with concomitant incorporation of data, included to analysis Chi-square test (p<0.05) for quantitative data and interpretation of meanings for qualitative. Variables: Birth weight, gestational age, Apgar score, complications, and length of hospital stay from 951 records of hospitalized premature infants; 18 mothers were interviewed during hospitalization, 15 days after discharge at home, 30 days after this at-home visit and at the age of 6 months of the child, by telephone, in Southern Brazil. Results: Identified as potential factors: Extreme prematurity and/or very premature, low birth weight, complications, and prolonged hospitalization. With the incorporation of the data, the relevance of these factors for children at risk of changes in development and behavior was verified. Mothers described their children as having healthy development but recognized prematurity is a factor that predisposes to new hospitalizations, and perinatal factors and those related to hospitalization contribute to the development of special health needs. Conclusion: The importance of early identification of factors that enhance the development of special health needs is understood to initiate the necessary stimuli to strengthen child development.